Pengaruh Dukungan Suami Terhadap Proses Adaptasi Fisik dan Psikologis Ibu Nifas - Kusumastuti, Ani; Junengsih, Junengsih; Oktalia, Juli (Jurnal Fisioterapi dan Kesehatan Indonesia, 2024)
The postpartum period begins with the birth of the baby and placenta. This is when a woman has an additional role as a mother. Changes that occur both physically and psychologically need to be facilitated so that various complications or disorders do not occur. Physical and psychological problems in postpartum mothers still often occur, such as postpartum infections and postpartum blues. This problem can have a big impact and even cause death if not handled properly. It is hoped that the support of the surrounding environment, especially the husband, can ensure the continuity of the postpartum mother's adaptation process, both physical and psychological adaptation, which can run well. The research aimed to determine the effect of a husband's support on the physical and psychological adaptation process of postpartum mothers. The research used a cross-sectional method on 50 postpartum mothers on days 7 to 14. The research instrument used a questionnaire filled out by respondents and observations of the mother's condition. The research results showed that there was a significant relationship between husband's support and physical and psychological adaptation in postpartum mothers, with a p-value <0.05.